Primary Aldosteronism More Prevalent in Patients With Cardioembolic Stroke and Atrial Fibrillation - Nguyen, Van; Tu, Tian Ming; Mamauag, Marlie Jane B.; Lai, Jovan; Saffari, Seyed Ehsan; Aw, Tar Choon; Ong, Lizhen; Foo, Roger S. Y.; Chai, Siang Chew; Fones, Shaun; Zhang, Meifen; Puar, Troy H. (Frontiers in Endocrinology, 2022)
Background Primary aldosteronism (PA) is the most common cause of secondary hypertension, and patients are at an increased risk of atrial fibrillation (AF) and stroke. We assessed the prevalence of PA in patients with recent stroke. Methods We recruited 300 patients admitted to an acute stroke unit with diagnosis of cerebrovascular accident (haemorrhagic/ischaemic) or transient ischaemic attack. Three months post-stroke, plasma renin and aldosterone were measured. Patients with an elevated aldosterone–renin ratio proceeded to the confirmatory saline loading test. Results Twenty-six of 192 (14%) patients had an elevated aldosterone–renin ratio. Three of 14 patients who proceeded to saline loading were confirmed with PA (post-saline aldosterone >138 pmol/l). Another three patients were classified as confirmed/likely PA based on the markedly elevated aldosterone–renin ratio and clinical characteristics. The overall prevalence of PA amongst stroke patients with hypertension was 4.0% (95% confidence interval (CI): 0.9%–7.1%). Prevalence of PA was higher amongst patients with cardioembolic stroke, 11% (95% CI: 1.3%–33%), resistant hypertension, 11% (95% CI: 0.3%–48%), and hypertension and AF, 30% (95%CI: 6.7%–65%). If only young patients or those with hypokalaemia were screened for PA, half of our patients with PA would not have been diagnosed. Our decision tree identified that stroke patients with AF and diastolic blood pressure ≥83mmHg were most likely to have PA. Conclusion We found that amongst hypertensive patients with stroke, PA was more prevalent in those with AF, or cardioembolic stroke. Screening for PA should be considered for all patients with stroke.